Mirage to Miraj: Opening Muslimerican Latitudes in Americanist Scholarship. (24th August 2020) - Marr, Tim
Abstract: What do Islamic perspectives and Muslim sensibilities disclose when they are integrated as elements of both US diversity and planetary transculturalism? This review essay appraises how four recently published books demonstrate different ways of writing Arab and Islamic angles of analysis into the ambit of US literary scholarship. They exemplify practices that help to overcome impediments of language, ideology, geography, and religion to derive emergent insights from a fuller consideration of Muslimerican expressions. Through their study of multiple forms of cultural expression, these authors help to lay out critical and creative latitudes that reveal some of the resources radiating from embodied Arab and Muslim ways of being in the world. By processing a parallax of perspectives about lived Islamic involvements through art and expression, these studies expose the poverty of the mirage and accustom readers to a Miraj of Muslimerican visions, a journey that opens for Americans a more comprehensive worldliness informed by human resources of religious imaginality. Their scholarship reveals postsecular and surprisingly progressive resources of ethics, dissent, and creativity that critical considerations of Muslimness provide for a broader transnationalism in US cultural and literary study.